Facilitating community building in learning networks through peer tutoring in ad hoc transient communities. (19th June 2007) - Kester, Liesbeth; Sloep, Peter B.; Van Rosmalen, Peter; Brouns, Francis; Kone, Malik; Koper, Rob
Learning in a so-called Learning Network is particularly attractive to self-directed learners, who themselves decide on their learning programme as well as the timing, pace and place of their studies. However, such learners may easily become isolated, which is detrimental to their studies. Furthermore, supporting them in their studies rapidly leads to staff overload. This paper discusses ad hoc transient communities as a means of tackling both problems. Such communities are well poised to enhance the sociability of a Learning Network and increase learning effectiveness.